Dual-field responsive polymer-dispersed liquid crystal films with polymer spacer columns and fluorescent properties. Issue 14 (14th November 2022) - Chen, Xianliang; He, Zemin; Li, Chunsheng; Miao, Zongcheng; Wang, Dong; Luan, Yi; Li, Yuzhan; Zhao, Yuzhen
ABSTRACT: Polymer dispersed liquid crystal (PDLC) films with polymer spacer columns were prepared by photomask stepwise polymerisation method. The effects of crosslinker content and liquid crystal (LC) content on the morphologies of polymer spacer columns and electro-optical properties of PDLC films were investigated. Due to the difference of crosslink density and system viscosity, the polymer spacer columns exhibit different morphologies and the electro-optical properties of PDLC films are also altered. Based on the above, the PVA coatings loaded with rare earth phosphor were introduced into PDLC films. The influences of rare earth phosphor concentration on the fluorescent and electro-optical properties of PDLC films were studied. Also, it was found that the UVaging resistance of PDLC films was enhanced because of the loading of rare earth phosphor absorbing UV light. Therefore, the successful preparation of PDLC films with polymer spacer columns and reversible fluorescence properties opens new possibilities for expanding the flexible display applications of PDLC. Graphical Abstract: uf0001